The Effects of 830 nm Light-Emitting Diode Therapy on Acute Herpes Zoster Ophthalmicus: A Pilot Study - Park, Kui Young (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2013)
BACKGROUND: Skin lesions and pain are the most distinctive features of herpes zoster. Light-emitting diode (LED) therapy is an effective treatment known for its wound-healing effects. OBJECTIVE: To determine whether the LED treatment affects wound healing and acute pain in acute herpes zoster ophthalmicus. METHODS: We recruited 28 consecutive Korean patients with acute herpes zoster ophthalmicus for the study. In the control group (group A), 14 subjects received oral famcyclovir. In the experimental group (group B), 14 subjects received oral famcyclovir and 830 nm LED phototherapy on days 0, 4, 7, and 10. In order to estimate the time for wound healing, we measured the duration from the vesicle formation to when the lesion crust fell off. The visual analogue scale (VAS) was used for the estimation of pain on days 4, 7, 10, and 14. RESULTS: The mean time required for wound healing was 13.14±2.34 days in group B and 15.92±2.55 days in group A (p=0.006). From day 4, the mean VAS score showed a greater improvement in group B, compared with group A. A marginal but not statistically significant difference in the VAS scores was observed between the two groups (p=0.095). CONCLUSION: LED treatment for acute herpes zoster ophthalmicus leads to faster wound healing and a lower pain score.